2006
DOI: 10.1002/ajmg.a.31539
|View full text |Cite
|
Sign up to set email alerts
|

Detection of low‐level mosaicism by array CGH in routine diagnostic specimens

Abstract: The advent of microarray-based comparative genomic hybridization (array CGH) promises to revolutionize clinical cytogenetics because of its ability to rapidly screen the genome at an unprecedented resolution. Yet, the ability of array CGH to detect and evaluate low-level mosaicism is not known. Our laboratory has analyzed over 3,600 clinical cases with the SignatureChip which we developed for the detection of microdeletions, microduplications, aneuploidy, unbalanced translocations, and subtelomeric and pericen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
199
2
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(222 citation statements)
references
References 21 publications
14
199
2
7
Order By: Relevance
“…33 It illustrates that such mosaicism, similar to our three patients with mosaic trisomy 9 (cases 25-27; Table 1), can be detected by CGH using blood sample DNA even though metaphase studies of blood lymphocyte cultures are completely normal. 10,34 The lowest HR-CGH-detected mosaicism grade was 15%, and this was found in a patient with trisomy 9 (case 27). Previously, mosaicism grade as low as 8% has been detected by 1 Mb array-CGH analysis.…”
Section: Mapping Of Chromosome Imbalances By Cgh H Lybaek Et Almentioning
confidence: 94%
“…33 It illustrates that such mosaicism, similar to our three patients with mosaic trisomy 9 (cases 25-27; Table 1), can be detected by CGH using blood sample DNA even though metaphase studies of blood lymphocyte cultures are completely normal. 10,34 The lowest HR-CGH-detected mosaicism grade was 15%, and this was found in a patient with trisomy 9 (case 27). Previously, mosaicism grade as low as 8% has been detected by 1 Mb array-CGH analysis.…”
Section: Mapping Of Chromosome Imbalances By Cgh H Lybaek Et Almentioning
confidence: 94%
“…Although it was suspected that array analysis would not be able to detect mosaicisms, the aCGH and SNP array techniques actually appear to be more sensitive in detecting low-level mosaicism than conventional karyotyping. 43,44 If mosaicism is not suspected, the number of cells counted with conventional karyotyping may not be sufficient to detect the aberrant subset of cells, and a single abnormal cell might be interpreted as an artifact of cell culture. 45 Two such cases of low-level mosaicism were reported in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that CMA may be more sensitive when abnormal cells fail to respond to mitogens and/or abnormalities are rare or absent in T cells, such as in PallisterKillian syndrome. 5,6 Five cases of mosaic trisomy, involving chromosomes 8, 9, 14, and 22, were detected only by CMA.…”
Section: Maximum Detection Of Mosaicism By a Conjunction Of Cma And Tmentioning
confidence: 99%